Perancangan Ulang Website Company Profile PT XYZ Menggunakan Framework Laravel dan Metode Waterfall - Anindya Khalisha Nurdianti; Rizky Parlika (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
PT XYZ is a company that offers software and application development services. PT XYZ's website faces several issues, including an unappealing visual appearance, disorganized homepage content, and an admin management system that is difficult to use independently. This research aims to redesign PT XYZ's website to be more modern, professional, responsive, and easily developed as a medium for the company to inform the public. The development was carried out using the Laravel framework, Bootstrap as a responsive CSS framework, MySQL as the database, and Firebase Analytics for monitoring visitor behavior. System testing was conducted using Black Box Testing. The results of the Black Box Testing on 12 test scenarios showed that all features functioned well. The system evaluation involved 30 respondents through a questionnaire whose validity was tested using Pearson Correlation and reliability using Cronbach's Alpha. The validity test results showed that all 10 statements were declared valid with calculated r values ranging from 0.450 to 0.752, all exceeding the table r value of 0.374 at a 5% significance level. The reliability test results showed a Cronbach's Alpha value of 0.82, thus the instrument was declared reliable. The redesigned PT XYZ website successfully meets all functional requirements and is suitable for use as a medium for the company's information and communication with the public.